From the Editor: On Women’s Health - Pacheco-Romero, José (2019)
Research on women’s health results in thousands of papers published inan infinite number of medical journals. It is not possible to read all thisnew literature and not all papers are open-access. In this section, we tryto summarize some of this investigation, knowledge that we may apply inour daily labor.